2018
DOI: 10.1186/s41983-018-0032-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of childhood and adolescence epilepsy in Upper Egypt (desert areas)

Abstract: BackgroundA high prevalence of epilepsy in children is frequently found in developing countries.ObjectiveThis study aimed to determine the prevalence and clinical pattern of childhood and adolescence epilepsy in Upper Egypt.MethodsThis is a door-to-door study conducted on all inhabitants < 18 years in Al Kharga district and Al Qusier city (36,195 subjects). The study was conducted through two stages; every stage consisted of two phases (screening and diagnostic).ResultsLifetime prevalence of childhood and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
4
25
0
1
Order By: Relevance
“…This went with Farghaly et al, who conducted a study to determine the prevalence and clinical pattern of epilepsy among children and adolescents in upper Egypt. This study demonstrated generalized seizures as the most frequent type in epileptic children and adolescents [16].…”
Section: Discussionmentioning
confidence: 52%
“…This went with Farghaly et al, who conducted a study to determine the prevalence and clinical pattern of epilepsy among children and adolescents in upper Egypt. This study demonstrated generalized seizures as the most frequent type in epileptic children and adolescents [16].…”
Section: Discussionmentioning
confidence: 52%
“…Cupper showed significantly higher level in epileptic cases when compared to control groups (p=0.002) Table (2).…”
Section: Resultsmentioning
confidence: 97%
“…Epilepsy begins in childhood in more than half of the cases. Approximately 50 million people in the world have epilepsy, up to rumrone -third of whom continue to have seizures despite appropriate drug treatment [2].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies from Egypt reported the prevalence of epilepsy among Egyptian children. A study reported that the lifetime prevalence of epilepsy in children below 18 years old was 9.7/1000 [6]. Another two studies reported a prevalence of 7-10/1000 among children at school who were less than 15 years of age [7,8], while another study reported a higher rate of 12.9/1000 among children < 12 years [9].…”
Section: Discussionmentioning
confidence: 99%